Guìa gastronómica del uso del Cabuyo en la parroquia Once de Noviembre, provincia de Cotopaxi - Garcia Pacheco, María Ximena (2021)
The present investigation began with the realization of a situational diagnosis of the study area corresponding to the Parroquia Eleventh de Noviembre of the use of the cabuyo in the preparation of ancestral dishes, with the aim of knowing the current situation in which this place is located within the four areas: socio-cultural, economic, environmental and tourist, the same ones that positively benefited the development of this investigative process. Next, the gathering of information from the parish GAD and the Development Plan and Territorial Ordering of the year 2016 (PDOT) was carried out. It should be noted that in the Parroquia Eleven de Noviembre the main economic activity is agriculture and livestock, with 29%, while the gastronomic and tourist activity is 1.8%, considered low, however in the place they are also dedicated to other activities such as: construction, commerce, vehicle repair, manufacturing industry. The parish has a population of 1988 inhabitants of which 58% are women while 42% are men distributed in ten neighborhoods which are Cristo Rey, San Pedro, Las Arenas, La Unión, San Gerardo, San Alfonso, Angamarca, Las Parcelas, Barrio Centro and La Libertad being their official language Spanish. The applied methodology was of a qualitative nature, applying techniques such as: interview, direct observation and question guide which contributed in the development of the study. In addition, an inventory was carried out for which the files obtained from the INPC Instructive (National Institute of Cultural Heritage), A4 Knowledge and Uses related to nature and the universe were used, obtaining as a result ten gastronomic techniques, of which 5 dishes belong to the daily gastronomy, 4 dishes to the occasional gastronomy and 1 dish to the festive gastronomy. The files include all the information revealing that it was necessary to carry out the inventory, with this it is desired to preserve the preparation of ancestral dishes with the use of cabuyo that are intangible heritage of this town. To finalize the final result of this research was the design of the gastronomic guide of the Parroquia Eleven de Noviembre, thanks to the support of the actors involved who provided the information in a detailed way which clearly provided the ingredients and the process of preparation of each dish. Finally, with this research, it is expected to contribute to future research in the Parish to rescue and safeguard the cultural and intangible heritage against the possible threats of globalization